2014
DOI: 10.1007/s11764-014-0375-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic morbidity and quality of life in survivors of childhood acute lymphoblastic leukemia: a prospective cross-sectional study

Abstract: Purpose Childhood acute lymphoblastic leukemia (ALL) is treated with potentially neurotoxic drugs and neurologic complications in long-term survivors are inadequately studied. This study investigated neurologic morbidity and its effect on quality of life in long-term survivors of childhood ALL. Methods Prospective, single institution, cross-sectional, institutional review board-approved study of long-term ALL survivors. Participants were recruited from institutional clinics. Participants answered an investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…Ramchandren et al . did not observe any impact on the quality of life of their cohort of ALL survivors despite evidence of electrophysiological neuropathy, while another study found that physical quality of life was not impaired in patients with clinical neuropathy . This is in contrast to our study in which ALL survivors with VIPN reported lower quality of life scores in the physical and social domains compared with those without VIPN.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Ramchandren et al . did not observe any impact on the quality of life of their cohort of ALL survivors despite evidence of electrophysiological neuropathy, while another study found that physical quality of life was not impaired in patients with clinical neuropathy . This is in contrast to our study in which ALL survivors with VIPN reported lower quality of life scores in the physical and social domains compared with those without VIPN.…”
Section: Discussioncontrasting
confidence: 99%
“…Neurophysiological studies have demonstrated increased distal latencies, decreased amplitudes of compound muscle action potentials and sensory nerve action potentials with little or no change in nerve conduction velocities in peripheral nerves following exposure to vincristine . Despite extensive studies on the neurotoxic effects of vincristine, there is still paucity of data on its long‐term effects in ALL survivors and its impact on function and quality of life in affected individuals . In addition, the evaluation and reporting methods have varied between studies, precluding any direct comparisons and conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported findings indicate that pain is a significant clinical problem for specific subgroups of childhood cancer survivors, such as bone cancer, CNS tumours, sarcoma, RMS, retinoblastoma and ALL survivors, for whom back pain was reported to be a frequent symptom . Previous studies have shown that back pain and neuropathy are associated with the number of times intrathecal chemotherapy is administered …”
Section: Discussionsupporting
confidence: 89%
“…Among ALL survivors, this may be related to increased use of intrathecal therapy to treat CNS disease in the more recent era. Data indicate that back pain is a frequent complaint of adult survivors of ALL (42), and that back pain and neuropathy are associated with the number of intrathecal chemotherapy administrations (43). In osteosarcoma survivors, this may be due to increases in numbers of younger patients eligible for limb-sparing related to availability of expandable prostheses in the 1990s, many of whom required multiple surgeries to manage orthopedic complications.…”
Section: Discussionmentioning
confidence: 99%